2022
DOI: 10.1002/14651858.cd013368.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Running shoes for preventing lower limb running injuries in adults

Abstract: Do different types of running shoes change the risk of developing a lower-limb injury? Key messagesNeutral / cushioned shoes may make little or no difference to the number of runners sustaining injuries or footwear satisfaction compared with minimalist shoes .It is uncertain if motion control shoes reduce the number of runners sustaining injuries compared with neutral/ cushioned shoes.Soft midsole shoes may make little or no difference to the number of runners sustaining injuries compared with hard midsole sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 137 publications
0
5
0
Order By: Relevance
“…While the unconverted foam outperformed the converted foams at the lowest impact energy of 1 J (due to its stress plateau limiting force), auxetic foam should be considered where impact severity is unpredictable and conventional foam may densify. Based on performance across various impacts, some potential applications for auxetic closed cell foams include contact sports, snowsports, cycling and running shoes; where the severity (shape, speed or mass of impacting bodies or surfaces) is variable and unpredictable [30, [97][98][99][100][101][102][103][104].…”
Section: Discussionmentioning
confidence: 99%
“…While the unconverted foam outperformed the converted foams at the lowest impact energy of 1 J (due to its stress plateau limiting force), auxetic foam should be considered where impact severity is unpredictable and conventional foam may densify. Based on performance across various impacts, some potential applications for auxetic closed cell foams include contact sports, snowsports, cycling and running shoes; where the severity (shape, speed or mass of impacting bodies or surfaces) is variable and unpredictable [30, [97][98][99][100][101][102][103][104].…”
Section: Discussionmentioning
confidence: 99%
“…To date, few interventions have resulted in a measurable decrease in injuries among runners. [15][16][17][18] Foundational to understanding why runners get injured is understanding how runners get injured. There are little data available for marathon runners throughout training and racing to determine when runners are more likely to experience injuries, what those injuries are (eg, anatomic location and tissue type), the effect of age on injury patterns and runners' healthcare utilisation for these injuries.…”
Section: Open Accessmentioning
confidence: 99%
“…Understanding why runners get injured is essential when creating injury prevention programmes. To date, few interventions have resulted in a measurable decrease in injuries among runners 15–18. Foundational to understanding why runners get injured is understanding how runners get injured.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, available scientific evidence regarding the main risk factors predisposing runners to suffer running-related injuries and injury prevalence is controversial and presents some limitations due to the heterogeneity of studies and quality of evidence [22,23]. Similarly, a recent review showed that most evidence failed to demonstrate a reduction in running-related injuries when comparing different types of running shoes, while there is no evidence that prescribing footwear based on foot type reduces these injuries [24]. Therefore, considering that the performance-RE-injury risk triaxial relationship is very complex, there is probably an optimal leg stiffness for each running speed given the runner's individual anthropometric characteristics.…”
Section: Introductionmentioning
confidence: 99%